Tissue culture system using a PANDA ring resonator and wavelength router for hydroponic plant - Kamoldilok, Surachart; Suwanpayak, Nathaporn; Suttirak, Saisudawan; Yupapin, Preecha P. (My University, 2012)
A novel system of nanofluidics trapping and delivery, which is known as a tissue culture system is proposed. By using the intense optical pulse(i.e., a soliton pulse) and a system constructed by a liquid core waveguide, the optical vortices (gradient optical fields/wells) can be generated, where the trapping tools in the same way as the optical tweezers in the PANDA ring resonator can be formed. By controlling the suitable parameters, the intense optical vortices can be generated within the PANDA ring resonator, in which the nanofluidics can be trapped and moved (transported) dynamically within the Tissue culture system(a wavelength router), which can be used for tissue culture and delivery in the hydroponic plant system. © 2011 IEEE.
Keywords: Hydroponics planting; nanofluidics; optical trapping; PANDA ring resonator; tissue culture